Differential Gene Expression Analysis of Bovine Macrophages after Exposure to the Penicillium Mycotoxins Citrinin and/or Ochratoxin A - Kristen M. Brennan; Se-Young Oh; Alexandros Yiannikouris; Daniel E. Graugnard; Niel A. Karrow (Toxins, 2017)
Mycotoxins produced by fungal species commonly contaminate livestock feedstuffs, jeopardizing their health and diminishing production. Citrinin (CIT) and ochratoxin A (OTA) are mycotoxins produced by Penicillium spp. and commonly co-occur. Both CIT and OTA can modulate immune response by inhibiting cell proliferation and differentiation, altering cell metabolism, and triggering programmed cell death. The objective of this study was to determine the effects of sublethal exposure (i.e., the concentration that inhibited cell proliferation by 25% (IC25)) to CIT, OTA or CIT + OTA on the bovine macrophage transcriptome. Gene expression was determined using the Affymetrix Bovine Genome Array. After 6 h of exposure to CIT, OTA or CIT + OTA, the number of differentially expressed genes (DEG), respectively, was as follows: 1471 genes (822 up-regulated, 649 down-regulated), 5094 genes (2611 up-regulated, 2483 down-regulated) and 7624 genes (3984 up-regulated, 3640 down-regulated). Of these, 179 genes (88 up-regulated, 91 down-regulated) were commonly expressed between treatments. After 24 h of exposure to CIT, OTA or CIT + OTA the number of DEG, respectively, was as follows: 3230 genes (1631 up-regulated, 1599 down-regulated), 8558 genes (4167 up-regulated, 4391 down-regulated), and 10,927 genes (6284 up-regulated, 4643 down-regulated). Of these, 770 genes (247 up-regulated, 523 down-regulated) were commonly expressed between treatments. The categorization of common biological functions and pathway analysis suggests that the IC25 of both CIT and OTA, or their combination, induces cellular oxidative stress, a slowing of cell cycle progression, and apoptosis. Collectively, these effects contribute to inhibiting bovine macrophage proliferation.